KIDNEY HEALTH IN SPORT: INVESTIGATING THE INFLUENCE OF CREATINE, CITRULLINE, L-ARGININE, BETA-ALANINE AND BRANCHED CHAIN AMINO ACIDS (BCAA) ON RENAL FUNCTION - Marta Korchowiec; Łukasz Bialic; Lidia Mądrzak; Katarzyna Krzyżanowska; Wiktor Chrzanowski; Julia Kwiecińska; Władysław Hryniuk; Jacek Sitkiewicz; Alicja Toczyłowska; Mateusz Muras (International Journal of Innovative Technologies in Social Science, 2025)
Aims: The purpose of this review was to examine how five commonly used supplements, including creatine, citrulline, L-arginine, beta-alanine, and branched-chain amino acids (BCAAs), affect physical performance and kidney health. These compounds are widely consumed in the context of athletic training, yet their long-term safety with respect to renal function remains insufficiently defined. Methodology: Relevant literature published between 1990 and 2024 was identified using PubMed, Scopus, and Google Scholar. The selection included studies describing the physiological effects and potential renal impact of each supplement. State of Knowledge: Analysis of the available research suggests that creatine does not impair kidney function in healthy individuals. Citrulline is considered metabolically safe and may support renal health in specific contexts, although elevated concentrations in patients with reduced kidney function could indicate metabolic imbalance. L-arginine may be beneficial in acute clinical settings but shows potentially harmful effects when used long term, especially in older or chronically ill individuals. Beta-alanine has demonstrated safety and antioxidant properties that could protect kidney cells. In contrast, high or prolonged intake of BCAAs may contribute to insulin resistance and worsen renal outcomes in people with diabetes or hereditary kidney disorders. Conclusions: When used appropriately by healthy individuals, these supplements are generally safe for kidney function. However, individual health status, dosage, and duration of use can significantly affect renal outcomes. BCAA supplementation, in particular, should be approached with caution in at-risk populations. More long-term studies are needed to fully assess the renal safety of these compounds in both athletic and clinical settings.